The Pricing Transmission Losses in Competitive Electricity Market in Bilateral Contract Market - Didi Istardi (Politeknik Negeri Batam, 2010)
In power system network, transmission losses is the main factor that must be consider in transportation energy from generator side to load side. In competitive electricity market, the pricing transmission losses must be allocated to the all market participants. This pricing must have economic efficiency on competitive operation of the power systems. Therefore, it is important to provide good methodologies that allow determining a loss allocation among market participants as accurate and fair as possible. In this paper, the transmission loss allocation will be implemented in bilateral contract market using several methods, pro rata, incremental loss allocation, proportional sharing, and unsubsidized marginal allocation.